Examples of artisric decoration of European manuscripts - Surmava, Marine ("Intercultural Dialogues" Transactions, 2025)
Medieval Europe inherited from antiquity the external form of the manuscript - the form of a book interwoven with scrolls and notebooks, which were widely used for compiling deeds and business documents. The development of cities in the life of Europe and, first of all, Italy in the 11th-15th centuries introduced a wide variety of documents. Originals of deeds signed and certified by a seal have come down to us. A greater number of copies are found in special capitulars, clerical registers and notarial minutes. A large number of scientific treatises tell about the intellectual life of medieval society. Humanists founded the most famous schools in Europe in Italy, where in the 13th-15th centuries they established courses for master calligraphers to copy books. One of the most famous calligraphers among the humanists was Petrarch. In addition to copyists, there were numerous groups of writers in the cities who drafted and formalized documents. They were called clerks, or notaries. The notary first drafted a working version, then copied it onto a piece of parchment, put his signature and a special mark called a paragraph. If the document concerned a business transaction, then witnesses were present at its drafting and confirmed it with their own signatures, and then they would certify it with a seal. As cities and administrative institutions grew, the number of notaries also increased. Every chancellery had its own notary. One of the oldest chancelleries was the papal chancellery. The numerous documents drawn up here were examples of symbols of both ecclesiastical and secular nature. In the 11th and 12th centuries, documents were written mainly on papyrus and parchment (wax was rarely used), and in some cases on paper. Papyrus, which was made from the pulp of the papyrus plant, was produced mainly in Egypt; after the Arabs conquered Egypt in the 7th century, it became difficult to import papyrus to Europe. The Merovingian kings wrote documents on papyrus until the second half of the 7th century, and the popes until the end of the 11th century.